If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = x + 0.7(10 + -1x) 8 = x + (10 * 0.7 + -1x * 0.7) 8 = x + (7 + -0.7x) Reorder the terms: 8 = 7 + x + -0.7x Combine like terms: x + -0.7x = 0.3x 8 = 7 + 0.3x Solving 8 = 7 + 0.3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.3x' to each side of the equation. 8 + -0.3x = 7 + 0.3x + -0.3x Combine like terms: 0.3x + -0.3x = 0.0 8 + -0.3x = 7 + 0.0 8 + -0.3x = 7 Add '-8' to each side of the equation. 8 + -8 + -0.3x = 7 + -8 Combine like terms: 8 + -8 = 0 0 + -0.3x = 7 + -8 -0.3x = 7 + -8 Combine like terms: 7 + -8 = -1 -0.3x = -1 Divide each side by '-0.3'. x = 3.333333333 Simplifying x = 3.333333333
| 9x+6=8x-2 | | x+2=3(x+6) | | (x-y)dx+(x+y)dx=o | | 3(2x-5)=2(5-3x) | | 3(7x+6)-4x=2(1-x) | | 2x-4y+10=0 | | 4=-s | | N+(n-3)=59 | | 7x+2x+7=20x-4 | | -4x+5-x=x-13 | | 4x+6=5x+15 | | 3-2x=133 | | 3-2x=130 | | 3(x-2)=(x-2)2 | | -4+5-x=x-13 | | 4y+3=2y-1 | | -15x^2+78x-15=0 | | (2y+1)2-(2y-1)2=16 | | 15x^2-78x-15=0 | | X(5)+y(3)=266 | | 3(x-1)+4=2(x+3)+1 | | 5(10-x)+20+6x=80 | | 3-2(x-1)=4-3(x+1) | | -8m^4-12m^3-1871m^2+636m-457=0 | | 6-3(x+1)=2+3(2x+3) | | 3(3x-2)=2(2x-5) | | -16m^4-24m^3-3742m^2+1272m-934=0 | | (4-x^2)dy-4ydx=0 | | f(t)=sin(2t)*cos(2t) | | 4(x-3)+5=9 | | 3x-3+4=6 | | 10-(50+x)=15 |